How children use spaces in the masjid? - Abu Bakar, Aniza; Zulkifely, Zur Atiqa; Abdul Majid, Noor Hanita; Ibrahim, Mohd Burhan (Abdullatif Al Fozan Award for Mosque Architecture, and Institut Terjemahan & Buku Malaysia Berhad, 2019)
Ramadhan is the best month to visit Masjid as many activities are organised to liven up the month. During this time of the year, many would take the opportunity to bring their children to experience tarawih, iftor (break-fasting) and Qiyamullail(staying up to perform ibadah) at Masjid. However, there have been some unpleasant sign towards the attendance of young children in masjid among the jamaah (congregational) members. This situation caused a challenge for families in engaging their children with masjid at their tender age. This study aims to identify and map the activities of the children during tarawih prayer at selected case studies masjids. Structured observation technique is applied. The observation recorded by mapping the activities and their locations on the layout plan and further supported with photos for further analysis. The findings suggest that the main activities of the children in masjid were praying, playing, sleeping, and sitting. Most of the time, they occupied the main prayer hall, the corridor, and the masjid compound. The study provides an insight into the influence of space types of activities by children in spaces of the masjid. Some masjid had approached the Jemaah before the prayer started to remind the parents to look after their children. Hence, many children choose to stay outside the prayer hall to avoid getting scold by the adult. From the observation, it can be concluded that spatial planning is indeed vital to ensure the children and masjid are well-connected and related to create a better Muslim community.